USE OF THE THEORY OF SIMILARITY FOR STUDYING OF REGULARITIES OF HETT EXCAHANGE WHEN DRYING A BEET PRESS - A. V. Drannikov; A. V. Kvasov; A. S. Polkanov; D. K. Kostina (Современная наука и инновации)
The drying process of beet pulp is influenced by temperature, the speed of superheated steam, the specific load of the material on the gas distribution grid and the pressure in the drying chamber. Subject to hydrodynamic and thermal similarity, taking into account scale factors, the similarity theory method allows you to extend the results of studies obtained on an experimental model to an industrial facility